Answer:
Simplifying 9m + -3 + -7m = 0
Reorder the terms: -3 + 9m + -7m = 0
Combine like terms: 9m + -7m = 2m -3 + 2m = 0 Solving -3 + 2m = 0
Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right.
Add '3' to each side of the equation. -3 + 3 + 2m = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 2m = 0 + 3 2m = 0 + 3 Combine like terms: 0 + 3 = 3 2m = 3
Divide each side by '2'. m = 1.5
Step-by-step explanation:
Hope this helps :)
Answer:
GET REKTTKTKTTK
Step-by-step explanation:
SJDHDIAJSJSJSJAJ
Answer:
{x,y}={8,5}
Step-by-step explanation:
12x + 12y = 156 4x + 6y = 62
Answer: x=1/2
Step-by-step explanation:
y= - 4x + 2
X=1/2
I really don't understand your question that you asked 3 WEEKS ago.